Early and late selection: Effects of load, dilution and salience - Tal Makovski (Frontiers Research Topics, 2014)
Our visual system is constantly bombarded by a variety of stimuli, of which only a small part is relevant to the task at hand. As a result, goal-directed behavior requires a high degree of selectivity at some point in the processing stream. The precise point at which selection takes place has been the focus of much debate. Early selection advocates argue that the locus of selection is at early stages of processing and that therefore, unattended stimuli are not fully processed. In contrast, late selection theorists argue that attention operates only after stimuli have been fully processed. Evidence supporting both sides has been accumulated over the years and the debate played a central role in the attention literature for decades. Perceptual load theory was put forward as an intermediate solution: the locus of selective attention depends on task requirements. When load is high, selection is early. When load is low, selection is late. This solution has been widely accepted and the early/late debate has been, for the most part, set aside. However, recently, perceptual load theory has been challenged on both theoretical and methodological grounds. It has been argued that it is not load, but rather perceptual dilution salience and other perceptual factors that determine the efficacy of attentional selection, which would call for a reevaluation of the current status of both perceptual load theory and its proposed alternatives, and more broadly, the early/late selection debate. The goal of this Research Topic is to provide an up-to-date overview of both empirical evidence and theoretical views on these key questions.